Apa yang Meningkatkan Kinerja Lingkungan Perusahaan? Model Konseptual Berbasis Investasi Hijau dan Tata Kelola Perusahaan - Susilo Adi; Agustinus Wardi (UNIVED Press, 2022)
This research seeks to improve the performance of green investment-based companies and good corporate governance to solve these problems developed a conceptual model Research methodology – The research was conducted through a survey using 112 respondents consisting of leaders of manufacturing companies in Indonesia. Then the concept model is developed and tested empirically. Results (Results): The hypotheses proposed in this study are all accepted and the empirical research model proposed in this study is the key strategy in improving the company's environmental performance based on futuristic thinking. Limitations:: Limitations in this study are, First, the questionnaire was sent via email. The second limitation is that this study does not consider the existence of other variables, and only focuses on Corporate Governance and the role of Green Investment as the interpening variable. Contribution: improvement of the Company's Environmental Performance which is facilitated by the concept of Green Investment as an interpening very relevant to be a key factor in improving the Company's Environmental Performance.